Prenatal Development of Sternum and Ribs of Buffalo - Lakshmi, J Bhagya; Ramayya, P Jagapathi; Rao, T. S. Chandrasekhara; Srilatha, Ch (Indian Journal of Veterinary Anatomy, 2012)
The cartilaginous precursor of sternum was noticed histologically at 54 days as the bilateral cores of cartilage cells. The earliest appearance of ossification was observed in 7th segment of sternum at 88 days of gestation. The 6th sternal segment showed ssification at 89 days. The last 4 segments of sternum i.e from 7th to 4th sternebra showed ossification at 92 days. Ossification began at 96 days in 3rd segment. At 59 days, ossification was first noted in the shaft (diaphysis) of the 2nd to 6th rib. At 64 days, diaphysis of all ribs i.e from 1st to 13th showed ossification.